What is the evidence-base for atopic eczema treatments? A summary of published randomised controlled trials - Nankervis, Helen; Thomas, K.S.; Delamere, Finola M.; Barbarot, S.; Smith, S.; Rogers, Natasha K.; Williams, Hywel C. (Wiley, 2016)
Atopic eczema (AE) is a common chronic inflammatory skin condition. Whilst many AE treatment options are available, the evidence to support their efficacy varies in depth and quality. In 2000, an NIHR HTA systematic review identified and evaluated existing randomised controlled trials (RCTs) of AE treatments. To ensure continuing utility, the NIHR commissioned an update to the review. Here, we present an overview of the updated report and key findings. Systematic reviews and RCTs of AE treatments that included participants with AE (criteria based or diagnosed) were identified using: MEDLINE, EMBASE, CENTRAL, LILACS, AMED, CINAHL and Cochrane Skin Group Specialised Register (searched to August 31st 2013 (RCTs) and 31st December 2015 (systematic reviews)). Outcome measures included: symptoms, AE severity, quality-of-life, and adverse effects. Study quality was assessed using the Cochrane Collaboration risk of bias tool. Of the 287 new RCTs identified, only 22 (8%) were judged to be low risk of bias. When combined with RCTs from the previous review (n= 254), we found ‘reasonable evidence of benefit’ for corticosteroids, calcineurin inhibitors, Atopiclair™, ciclosporin, azathioprine, ultraviolet light and education programmes. Interventions with reasonable evidence of ‘no benefit’ included some dietary interventions, ion exchange water softeners, multiple daily applications of topical corticosteroids and antibiotic-containing corticosteroids for non-infected AE. Many common treatments lack evidence of efficacy and warrant further evaluation. The evidence base for AE is still hampered by poor trial design and reporting. The trials included in this review were used to establish the Global Resource of Eczema Trials (GREAT) Database.